FORMATION OF A PERSONALITY WITH HYPOCHONDRIAL DISORDERS IN THE ASPECT OF SPECIALISTS’ PROFESSIONAL TRAINING - Vysnyuk, Inessa (PSYCHOLOGICAL JOURNAL, 2019)
The paper analyzes the theoretical and methodological problems of psychological health and professional development. The areas of this phenomenon studies in the psychological literature are identified. The paper examines the correlations between an individual’s professional work and his/her mental health. Mental health preservation is only possible at mutual correspondence of professional requirements and personal potentials; the most important among them is psychological stability. The potential risks and deviational manifestations are analyzed for different professions and the corresponding violations. In the case of an adequate correlation of the above structures, professional work can stimulate creativity and its development and promote psychosomatic health. Based on our research results, an optimal profession choice is possible in the case of conformity of stable personal structures (here, the main place belongs to psychological stability) with professional requirements and adaptation of variable personal traits (dependent on environmental influences, formed at training, education and professionalization) to professional work. It should be noted that the normative correlative indicators show that there are differences in formed personal equilibrium of different people even in the case of their health. In the presence of a somatic pathology, different intensities and different types of correlations appear: some correlations are more intensive and others become attenuated. During a disease, restructuring, changes in informational and energy components of a state occurs. Hypochondriacal disorders can be a prerequisite for somatic diseases, as it has been proven. Their primary genesis is nosological manifestations that reflect an individual’s central experience concerning disease severity. In the case of their occurrence as a number of concomitant symptoms, we should note their fluidity as a syndrome. Somatic diseases are not direct models of personal experiences, but reflect a complex and indirect process. Changes occur in the very states that are interpreted in hypochondrial disorders.